Prognostic evaluation of perinephric fat, renal sinus fat, and renal vein invasion for patients with pathological stage T3a clear‐cell renal cell carcinoma. (9th September 2018) - Shah, Paras H.; Lyon, Timothy D.; Lohse, Christine M.; Cheville, John C.; Leibovich, Bradley C.; Boorjian, Stephen A.; Thompson, R. Houston
Abstract : Objective: To investigate the prognostic significance of various patterns of extrarenal extension that comprise pathological stage T3a clear‐cell renal cell carcinoma (ccRCC) amongst patients undergoing nephrectomy for non‐metastatic disease. Patients and Methods: A retrospective review of 563 patients who underwent radical nephrectomy for pathologically confirmed T3aN0/NxM0 ccRCC between 1970 and 2011 was performed. All pathological slides were re‐reviewed by one urological pathologist. Associations of patterns of extrarenal extension (perinephric fat [PF], renal sinus fat [SF], and renal vein [RV], in isolation or in any combination) with disease progression, cancer‐specific mortality (CSM), and all‐cause mortality were evaluated on multivariable analyses. Results: Overall, PF invasion, renal SF invasion, and RV tumour thrombus were present in 144 (26%), 51 (9%), and 163 (29%) patients, respectively, with multiple patterns of extrarenal extension identified in 205 (36%) patients. There were no significant differences in survival outcomes for isolated involvement of PF, renal SF, or RV. However, patients with multiple patterns of extrarenal extension were at significantly increased risk of disease progression (hazard ratio [HR] 1.31, 95% confidence interval [CI] 1.04–1.65; P = 0.020), CSM (HR 1.64, 95% CI 1.27–2.12; P < 0.001), and all‐cause mortality (HR 1.32, 95% CI 1.08–1.61; P = 0.008). Conclusions: The presence of multiple patterns of extrarenal extension is associated with a higher risk of disease progression and cancer‐related death after radical nephrectomy compared to isolated involvement of the PF, renal SF, or RV, which carry similar prognostic weight. If validated, these findings may help refine risk stratification of non‐metastatic T3a RCC by distinguishing patients with multiple vs one pattern of extrarenal extension.